How to distribute antidote to control epidemics - Borgs, Christian; Chayes, Jennifer; Ganesh, Ayalvadi; Saberi, Amin (2008)
We give a rigorous analysis of variations of the contact process on a finite graph in which the cure rate is allowed to vary from one vertex to the next, and even to depend on the current state of the system. In particular, we study the epidemic threshold in the models where the cure rate is proportional to the degree of the node or when it is proportional to the number of its infected neighbors.